2016
DOI: 10.1039/c6ee02266a
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and nuclear contributions to time-resolved optical and X-ray absorption spectra of hematite and insights into photoelectrochemical performance

Abstract: Spectra show both transient photocarriers and lattice heating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
154
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(168 citation statements)
references
References 101 publications
14
154
0
Order By: Relevance
“…As discussed in Hayes et al 28 , the photogeneration yield of hematite changes considerably across the spectrum due to excitations that generate mobile charge carriers (LMCT bands) and excitations that do not (d-d transitions), depending on the wavelength. Considering the LMCT bands reported by Hayes et al 28 , the optimal spectral window for extracting the f(z) profile is between 356 and 396 nm, where LMCT transitions account for more than 93% of the total optical absorption.…”
Section: From Well-known Materials To Poorly Understood Onesmentioning
confidence: 99%
See 4 more Smart Citations
“…As discussed in Hayes et al 28 , the photogeneration yield of hematite changes considerably across the spectrum due to excitations that generate mobile charge carriers (LMCT bands) and excitations that do not (d-d transitions), depending on the wavelength. Considering the LMCT bands reported by Hayes et al 28 , the optimal spectral window for extracting the f(z) profile is between 356 and 396 nm, where LMCT transitions account for more than 93% of the total optical absorption.…”
Section: From Well-known Materials To Poorly Understood Onesmentioning
confidence: 99%
“…For example, in transition metal oxides such as hematite (a-Fe 2 O 3 ) and copper vanadate (g-Cu 3 V 2 O 8 ), considered as potential photoelectrode candidates for PEC cells for solar water splitting, it has been reported that d-d transitions produce excited states that are site localized and hence cannot be harvested efficiently as useful photocurrent. [28][29][30][31] However, other transitions, such as ligand-to-metal charge transfer (LMCT) transitions, give rise to mobile charge carriers that contribute more effectively to the photocurrent. 28,31 Thus, different types of transitions yield different probabilities of the photogenerated charge carriers to contribute to the photocurrent, such that the effective charge carrier generation function, G, depends not only on the amount of light absorbed but also on the type of the electronic transition induced by the absorbed photons.…”
Section: Sce Profilementioning
confidence: 99%
See 3 more Smart Citations